Curriculum Evaluation and Development: A Systematic Approach to Literature Review in Educational Management - Maryati, Mimin; Ferianto, Ferianto; Suryana, Sayan; Makbul, M.; Munafiah, Nida’ul (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This study aims to investigate the evaluation and development of curriculum in education management through a systematic literature review (SLR). The study also seeks to identify gaps in the academic literature and make essential contributions to filling those knowledge gaps. Data was collected through a literature search on Google Scholar for articles published in Scopus-indexed journals. After screening with inclusion and exclusion criteria, 21 relevant articles were analyzed using NVivo software. This analysis includes identifying trends, distribution, research contributions, and the methodology used in these studies. Research trends show an increased interest in curriculum evaluation and development in recent years, reflected in the increasing number of research articles. The distribution of research articles by publisher, journal, and country of origin demonstrates the diversity of publication sources and international contributions in the academic literature on curriculum management. The analysis also revealed the diversity of research methodologies, covering a wide range of quantitative and qualitative methods. In addition, the use of software for data analysis is also highlighted in this study, showing a trend in the use of technology in facilitating research analysis. This study concludes that curriculum evaluation and development in education management is a complex and crucial topic, requiring a multidimensional approach and cross-border cooperation to understand it profoundly and overcome existing challenges. The study identifies gaps in the academic literature and provides a basis for further research and practice in curriculum evaluation and development.